2013
DOI: 10.1017/s0376892912000434
|View full text |Cite
|
Sign up to set email alerts
|

Biosphere Reserves for conservation and development in Ukraine? Legal recognition and establishment of the Roztochya initiative

Abstract: SUMMARYThe Biosphere Reserve (BR) concept is an approach that simultaneously reconciles and promotes conservation of natural and cultural diversity, environmentally and socioculturally sustainable economic development, and research. This study focuses on the legal recognition of the BR concept as a tool for sustainable development (SD) in Ukraine, and what impact legislation has had on BR implementation. The BR concept has been incorporated into Ukrainian nature conservation legislation. However, interviews wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…The forest types are very diverse and range from dry sites with Scots pine to mesic sites with beech to wet sites with ash [ Fraxinus excelsior L.] and black alder [ Alnus glutinosa L.] [ 56 ]. Recently, a major part of this territory was designated as a MAB UNESCO Biosphere Reserve “Roztochya” [ 57 , 58 ]. There are 120 settlements in Roztochya with about 60,000 inhabitants (Yavorivskiy and Zhovkivskiy rayons).…”
Section: Methodsmentioning
confidence: 99%
“…The forest types are very diverse and range from dry sites with Scots pine to mesic sites with beech to wet sites with ash [ Fraxinus excelsior L.] and black alder [ Alnus glutinosa L.] [ 56 ]. Recently, a major part of this territory was designated as a MAB UNESCO Biosphere Reserve “Roztochya” [ 57 , 58 ]. There are 120 settlements in Roztochya with about 60,000 inhabitants (Yavorivskiy and Zhovkivskiy rayons).…”
Section: Methodsmentioning
confidence: 99%
“…This complicates co-ordination among neighboring land owners, which results in short-term commitments to manage individual wet grassland patches, which often have several land owners. Additionally, different levels of governance are poorly integrated [135,136]. We emphasize the need for integrated studies that assess the present governance process and its outputs in terms of management actions, and finally the consequences on the ground, such as wet grasslands as a functional green infrastructure for viable populations of waders (see [16]).…”
Section: Towards Governance Of Wet Grasslands As a Green Infrastructurementioning
confidence: 99%
“…Lack of awareness in the community of the BR concept leads to the local misperception about the difference between the main aims of the conventional PA management and the BR model. This has two consequences, firstly, similar to findings from many other studies (e.g., Fraga, 2006;Wallner et al, 2007;Bosak, 2008;Kusova et al, 2008;Elbakidze et al, 2013), we found that lack of understanding of the BR model leads to the fears of local stakeholders that the BR will limit exploitation and use of forest, land and natural resources for socio-economic development in the province. Secondly, confusion about how a BR should work on the ground (UNESCO, 2010;Reed and Egunyu, 2013) leads to lost opportunities to exploit the potential advantages of the BR to promote conservation and local economic development, while BR management is concerned about the deregistering of the BR title by UNESCO if their international criteria and instructions are not met.…”
Section: Discussionsupporting
confidence: 88%